Evaluasi Pertambahan Bobot Badan Sapi Aceh Jantan yang Diberi Imbangan Antara Hijauan dan Konsentrat di Balai Pembibitan Ternak Unggul Indrapuri - Yunasri Usman; Eka Meutia Sari; Nuzul Fadilla (Agricultural Faculty, 2013)
The evaluation of the Aceh cattle bulls weight which compensated between forage and concentrate at Superior Livestock Place in IndrapuriABSTRACT. This research was conducted at Superior Livestock Place in Indrapuri District, Aceh Besar which lasted for 42 days. It was started on November 28th 2012 until January 9th 2013. This research was aims to know about the average daily gain for Aceh cattle bulls which compensated between forage and concentrate by using 12 bulls aged 2-2,5 years old. The design was used a Randomized Design Groups with 4 feed treatments and 3 repetitions. The feed percentages between forage and concentrate are ration A (100% forages), B (80%)forages and 20% concentrates), C (60% forages and 40% concentrates), and D (40% forages and 60% concentrates). The research analysis data were obtained by using ANOVA (Analysis of Variance). The parameters which observed in this study was the average daily gain, consumption, conversion, and efficiency rations. The result showed that the ration dry matter intake highly significantly (P0,01) between treatment A (4,45 Kg), and B (3,61 Kg), C (2,72 Kg), and D (3,38 Kg), but the treatment B and D highly significantly than treatment C (P0,01), the best ration consumption were derived from treatment C. The body weight Kg/bull/day significantly (P0,05) between treatment A (0,47 Kg) and B (0,65 Kg), C (0,60 Kg), and D (0,61 Kg), the best average daily gain were derived from treatment B. The conversion ration showed that highly significantly (P0,01) between treatment A (9,55 Kg), and B (5,55 Kg), C (4,60 Kg), and D (5,59 Kg), the best ration conversion were derived treatment C. Similarly, the efficiency ration showed that highly significantly (P0,01) between treatment A (0,11%), and B (0,18%), C (0,22%), and D (0,18%), C is the best ration efficiency on the treatment.